Preparasi Kromosom Fase Mitosis Markisa Ungu (Passiflora edulis) Varietas Edulis Sulawesi Selatan - Muhlisyah, Nurul; Muthiadin, Cut; Farhatul Wahidah, Baiq; Rasdianah Aziz, Isna (Biogenesis: Jurnal Ilmiah Biologi, 2014)
Passion fruit (Passifloraceae) was derived from tropical South America. Kind of passion fruit that widely cultivated in South Sulawesi is purple passion fruit (Passiflora edulis). This study aimed to observe the activity of Passiflora edulis chromosome at different stages of cell division and observed active mitosis time. The study was conducted by using exploratory descriptive study and obtained results a mitotic on Passiflora edulis occurs at 09.00 until 15.00 pm. Prophase seen in 5 minute after observation, prometaphase in 80 minute after the first observation, metaphase in 154 minutes after the first observation, anaphase in 227 minutes after the first observation, and telophase in 317 minutes after the first observation.Keywords: Chromosome, Mitosis, Passiflora edulis, Purple Passion Fruit